Inter-comparison of boron concentration measurements at INFN-University of Pavia (Italy) and CNEA (Argentina) - Portu, Agustina Mariana (2015)
An inter-comparison of three boron determination techniques was carried out between laboratories from INFN-University of Pavia (Italy) and CNEA (Argentina): alpha spectrometry (alpha-spect), neutron capture radiography (NCR) and quantitative autoradiography (QTA). Samples of different nature were analysed: liquid standards, liver homogenates and tissue samples from different treatment protocols. The techniques showed a good agreement in a concentration range of interest in BNCT (1-100. ppm), thus demonstrating their applicability as precise methods to quantify boron and determine its distribution in tissues.